Heat Waves Are a Major Threat to Turbid Coral Reefs in Brazil - Duarte, Gustavo A. S.; Villela, Helena D. M.; Deocleciano, Matheus; Silva, Denise; Barno, Adam; Cardoso, Pedro M.; Vilela, Caren L. S.; Rosado, Phillipe; Messias, Camila S. M. A.; Chacon, Maria Alejandra; Santoro, Erika P.; Olmedo, Daniele B.; et al. (Frontiers in Marine Science, 2020)
Coral reefs are threatened by climate change on a global scale with thermal-stress events and mass coral bleaching being widely reported. The reefs off the east coast of Brazil (and other turbid areas) have, however, historically escaped such thermal-stress events, with relatively low levels of background coral mortality (5-10%). This has recently changed. Here we show that, in 2019, degree heating weeks (DHW) of 19.65 coincided with catastrophic declines in coral cover, especially in the major reef building hydrocoral Millepora alcicornis. The decline was due to bleaching associated with exposure to high temperature stress culminating in DHW values exceeding 15 for a period of 50 days. At two independent sites, surveys showed upwards of 83.5  9.0% and 89.1  3.9% mortality, and at a third site showed relatively lower (albeit still high), mortality rates of 43.3  12.0% were recorded. The mass die-off in 2019 is unprecedented in the South Atlantic reefs and coincides with increased heating events.